Technological Change and Public Policy Agenda Setting: The Broadband Regulation for Universalization in Brazil - Rauen, Christiane Vianna (Law, State and Telecommunications Review, 2011)
This paper analyzes the influence of technological change on the public policy agenda setting, especially on the regulatory agenda. In doing so, it analyzes how technological changes that took place in the telecommunication sector have altered the forms of communication in society and how they have imposed changes on the scope of regulatory agenda for universalization (from fixed telephony to broadband services). This analysis is based on a bibliographical and legal framework review. One can observe that, considering technologically dynamic sectors, as telecom, the regulatory agenda for universalization is at odds with technical changes. Thus the constant revision of these agendas is of major importance, so the regulatory entity can guarantee that the universalization of telecom services will constantly be in line with its technological advances.